The complete plays of sophocles : a new translation - Sophocles (Harper Perennial, 2014)
The most celebrated plays of ancient Athens in vivid and dynamic newtranslations by award-winningpoets Robert Bagg and James Scully The dominant Athenian playwright in fifth-century-BCE Athens, Sophocles left us seven powerful dramas that still shock as they render the violence that erupts within divinity and humankind. oedipus the King, oedipus at Kolonos, and Antigone trace three generations of a family manipulated by the inscrutably vindictive god Apollo to commit patricide, incest, and kin murder. Elektra and Women of Trakhis begin as studies of women obsessed with hatred and desire but become dissenting critiques of the Greeks' enthusiasm for revenge and ego-crazed heroics. Two hard-hitting dramas set in war zones, Aias and Philoktetes, use conflicts among Greek warriors at Troy to thrash out political and ethical crises confronting Athenian society itself. These translations, modern in idiom while faithful to the Greek and already proven stageworthy, preserve the depth and subtlety of Sophocles' characters and refresh and clarify his narratives. Their focus on communities under extreme stress still resonates deeply for us here and now. This is Sophocles for a new generation entering the turbulent arena of ancient Greek drama.